Quantum chemistry - Levine, Ira N. (New Delhi: PHI Learning Private Limited, 2009)
The Sixth Edition of this widely used textbook presents quantum chemistry for advanced graduate and beginning postgraduate students. The subject is carefully explained step-by-step, allowing students to easily follow the presentation. Necessary mathematics is reviewed in detail. Worked examples aid learning. A solutions manual for the problems is available. Extensive discussions of modern abinitio, density functional, semiempirical, and molecular mechanics methods are included.
Appendix 719-721p.; Bibliography 722-724p.; Index 731-751p.